Strengthening Supply Chain Operational Performance through Relational and Organizational Culture Capabilities - Lee, Khai Loon; Nawanir, Gusman; Zahari, Abu Bakar; Jalal, Hanaysha (ExcelingTech Pub, UK, 2019)
In today’s dynamic business environment, the competition is no longer between firm, but between supply chains to gain competitive advantages. The trends have made industrial practitioners focusing more on the key factors influencing the performance of the supply chain operation. The powers of relational capability in managing supply chain have gained an incredible attention from researchers and practitioners because of the benefits of supply chain performance. However, the influences of organizational culture capability is equally critical for supply chain performance to keep growing. This paper makes an initial attempt to identify the critical success factors of supply chain operational performance amongst textile and apparel companies in Malaysia. The total of 201 questionnaires were sent to Malaysia's textile and apparel company that is listed in the Federation of Malaysian Manufacturers (FMM) and Malaysian External Trade Development Corporation (MATRADE) directory. The total of 121 usable responses were obtained and analyzed through Statistical Package for Social Science (SPSS). The discussion of this study is followed by presenting the results of survey on the relationship of relational capability and organizational culture capability on supply chain operational performance. The results shown that the relationship between relational capability and organizational culture capability have significant impact on the performance of supply chain operation.